2023
DOI: 10.3389/fimmu.2022.1077414
|View full text |Cite
|
Sign up to set email alerts
|

Fire in the belly: A scoping review of the immunopathological mechanisms of acute pancreatitis

Abstract: IntroductionAcute pancreatitis (AP) is characterised by an inflammatory response that in its most severe form can cause a systemic dysregulated immune response and progression to acute multi-organ dysfunction. The pathobiology of the disease is unclear and as a result no targeted, disease-modifying therapies exist. We performed a scoping review of data pertaining to the human immunology of AP to summarise the current field and to identify future research opportunities.MethodsA scoping review of all clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 239 publications
(276 reference statements)
0
8
0
Order By: Relevance
“…Similar to what happens in SIRS, peripheral blood lymphocyte depletion in acute pancreatitis may result from both excessive apoptosis and migration to the site of inflammation as has been previously hypothesized [29,30]. Regarding more detailed lymphocyte profiling, most studies have explored T lymphocytes, showing that acute pancreatitis results in the systemic activation of T cells [31,32]. Among T cells, it has been shown that there is a significant depletion of the CD4 + population, while CD8 + cell levels were reported to be present in the normal ranges [29].…”
Section: Discussionmentioning
confidence: 89%
“…Similar to what happens in SIRS, peripheral blood lymphocyte depletion in acute pancreatitis may result from both excessive apoptosis and migration to the site of inflammation as has been previously hypothesized [29,30]. Regarding more detailed lymphocyte profiling, most studies have explored T lymphocytes, showing that acute pancreatitis results in the systemic activation of T cells [31,32]. Among T cells, it has been shown that there is a significant depletion of the CD4 + population, while CD8 + cell levels were reported to be present in the normal ranges [29].…”
Section: Discussionmentioning
confidence: 89%
“…Inflammatory mediators further secrete by infiltrating immune-related cells, increase vascular permeability, cause neutrophil extravasation and activation, edema and microvascular disorder, and ultimately lead to hypoxia and tissue damage. 20 The results of this study showed that the levels of seven out of 12 cytokines were significantly higher in the SAP group than in the mild or moderate AP group, namely IL-1β, IL-5, IL-6, IL-8, IL-10, IL-17, TNF-α. Some studies have pointed out that among the many cytokines, TNF-α is the earliest and most widely biologically effective cytokine, and also a key factor in causing SIRS and complications.…”
Section: Discussionmentioning
confidence: 62%
“…Damaged acinar cells release damage‐associated molecular patterns, which are recognized by pattern recognition receptors (PRRs), and PRRs activate tissue and peripheral blood leukocytes and trigger the release of inflammatory cytokines. Inflammatory mediators further secrete by infiltrating immune‐related cells, increase vascular permeability, cause neutrophil extravasation and activation, edema and microvascular disorder, and ultimately lead to hypoxia and tissue damage 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute pancreatitis is an inflammatory disease of the exocrine pancreas, which may develop under sterile conditions and is thought to be instigated by acinar cell injury [ 1 , 2 ]. Apart from transient obstruction of the pancreatic ducts by gallstones, which causes bile to enter the pancreatic ductal tree, the most common causes of acute pancreatitis are alcohol abuse and hypertriglyceridemia [ 2 , 3 ]. The inflammatory response may resolve without specific treatment within a few days, or progress to systemic inflammation, culminating in a life-threatening failure of organs outside the pancreas [ 2 ].…”
Section: Introductionmentioning
confidence: 99%